An Analysis of Code Mixing Used By Indonesian Bts Army on X - Siti Nurhalisa (Fakultas Ilmu Budaya, 2024)
The phenomena of code mixing have become a societal trend or style. This style was investigated in sociolinguistics. This phenomenon is found on the tweets of BTS ARMY fan. Therefore, this study discusses the code mixing that is used by a group of K-POP fan called ARMY through their tweets on X. This study aims to determine the types of code mixing used by ARMY and to reveal the reasons behind the using of code mixing in their tweets. This study takes sixty nine tweets from four different accounts to be analyzed. The results show that the Insertion type got the highest score rather than others. This study also found that the reasons of using mixing code are Intentions to clarify the content of the speech for the interlocutor and Repetition. Mixing the code could avoids misunderstanding because some readers/audiences/followers are coming from different background.
Reupload Repository 26 Februari 2026_Hasyim/Firdiana
Keywords: Mixing Code; BTS ARMY